Stage-Level and Individual-Level distinction in morphological variation - Rivas, Javier; Brown, Esther L. (Borealis – An International Journal of Hispanic Linguistics, 2012)
This work examines the role of the stage-level (SL)/individual-level (IL) distinction applied to nouns in a case of morphosyntactic regularization in Spanish: variable reanalysis of the NP argument as subject in the presentational haber construction (había/habían perros). We conduct variationist, quantitative analyses on all instances of existential haber with a plural NP in corpora of spoken Puerto Rican Spanish (>500,000 words) to determine the linguistic factor groups that promote reanalysis and, hence, pluralized forms. Results of variable rule analyses reveal that the SL-IL distinction constrains the regularization. IL predicates significantly favor haber regularization (e.g., habían muchas personas de las Antillas ‘there were a lot of people from the Antillas’) whereas SL predicates significantly disfavor pluralized forms (este año hubo menos tiros que en años pasados ‘this year there were fewer shots fired than previous years’). These results are interpreted from within a usage-based framework in which the status of the noun introduced in the [haber + NP] construction, as either a likely or unlikely subject for haber, influences the analogical leveling. IL predicates are more prototypical nouns than SL predicates because the former are temporally persistent. IL predicates promote nouns’ candidacy as subjects over direct objects because prototypical subjects present two temporally-persistent characteristics: independence existence and referentiality. As a result, IL predicates increase the likelihood of reanalyzing the direct object as subject, thus triggering agreement of the verbal form with plural NPs. SL predicates, on the other hand, because they display low temporal stability, inhibit regularization.